Studies on the feasibility of bisphenol-A removal and its kinetics using Pseudomonas aeruginosa in both flask and an inverse fluidized bed reactor. Issue 2 (1st February 2023) - M, Venkatesh Prabhu; S, Balasubramanian; Kapoor, Ashish; Joshi, Ketki; Joshi, Keya; Shariffa, Nasrin
Abstract: A rapid increase in global industrialization has resulted in the extensive use of bisphenol-A (BPA). The presence of BPA in the environment resulting from the discharge of industrial effluents affects the quality of surrounding land and water bodies. Continuous exposure of BPA into the environment affects human health because BPA is an endocrine-disrupting chemical. Therefore, the removal of BPA has become considerably crucial to protect the environment and human health. This study examined the effect of the most important parameters, namely pH, temperature, inoculum size, and substrate concentration, on BPA removal. Pseudomonas aeruginosa was used in this study, under free (non-immobilized) and immobilized conditions. Batch experiments using an Erlenmeyer flask were conducted to optimize conditions for the maximum removal of BPA. A BPA concentration of 0.2 mg/mL, inoculum size of 0.8 mL, a temperature of 35 °C, and a pH of 7 were the optimum conditions for the maximum BPA removal. Under these conditions, the maximum BPA removal was observed in immobilized P. aeruginosa compared with non-immobilized cells (free cells of P. aeruginosa ). Furthermore, the feasibility of BPA removal on a large scale was determined using an inverse fluidized bed reactor (IFBR) with a working volume of 4 L and polypropylene as the carrier material operating under a batch mode. Hydrodynamic and mass transfer experiments were performed, and operating parameters, namely superficial gas velocity, percentage of bed expansion, and holdups, were optimized. The rate constants were calculated as 0.011 and 0.0946 h −1 in IFBR and Erlenmeyer flask experiments, respectively.